(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The study analyzed polymorphisms of folate cycle genes (MTHFR, MTR, MTRR) in women with congenital malformations (CM) of the fetus and non-viable pregnancy. It was found that the homozygous mutant genotype C/C (Glu429Ala, MTHFR) was found 2.5 times more often in the group of women with CM of the fetus than in the control group. The genotype G/G (Ile22Met, MTRR) was found 4.6 times more often in women with CM of the fetus compared to the control. The obtained data confirm the role of mutations in folate cycle genes in the development of reproductive complications, and also indicate the need to take into account endo- and exogenous factors that contribute to their implementation.